2007
DOI: 10.1021/ol7021017
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Carbon−Oxygen Bonds by Palladium:  Toward a Mild, Catalytic Approach to α-Amino Acid Derivatives

Abstract: A Lewis acid mediated method to induce the carbon-oxygen bond of amide-substituted ethers to undergo addition to palladium is described. The product of this reaction has been crystallographically characterized. This reaction suggests the potential use of such ethers as an alternative to organic halides in palladium catalyzed carbon-carbon bond formation. As an illustration of this potential, this reaction has been used to design a mild, catalytic route to alpha-amino acid derivatives from alpha-phenoxyamides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
10
2
Order By: Relevance
“…AlF 3 ) to activate the substrate toward oxidative addition. [4,5] Considering the availability of a-amidoethers as building blocks, we became interested in the potential use of this chemistry to access other classes of products. In particular, we recently reported that the multicomponent coupling of imines, acid chlorides, and carbon monoxide with unsaturated substrates can provide a route to assemble various useful heterocycles (pyrroles, imidazoles, imidazolines, or b-lactams) by the formation of the münchnones (3).…”
Section: Yingdong Lu and Bruce A Arndtsen*mentioning
confidence: 93%
See 2 more Smart Citations
“…AlF 3 ) to activate the substrate toward oxidative addition. [4,5] Considering the availability of a-amidoethers as building blocks, we became interested in the potential use of this chemistry to access other classes of products. In particular, we recently reported that the multicomponent coupling of imines, acid chlorides, and carbon monoxide with unsaturated substrates can provide a route to assemble various useful heterocycles (pyrroles, imidazoles, imidazolines, or b-lactams) by the formation of the münchnones (3).…”
Section: Yingdong Lu and Bruce A Arndtsen*mentioning
confidence: 93%
“…[1] One useful feature of this reaction is the accessibility of the substrates (1), or their ether analogues, for use in carbonylation reactions. These are presumably related to the poor ability of palladium to directly activate the C À O bond of 1, which instead is believed to be converted into a more reactive iminium salt intermediate (4) under the reaction conditions (Scheme 2). [2] The coupling of this synthesis with catalytic carbonylation allows the formation of amino acid derivatives, which have various substitutions, in a minimal number of steps and on large scale.…”
Section: Yingdong Lu and Bruce A Arndtsen*mentioning
confidence: 99%
See 1 more Smart Citation
“…AlF 3 ) to activate the substrate toward oxidative addition. [4,5] Considering the availability of a-amidoethers as building blocks, we became interested in the potential use of this chemistry to access other classes of products. In particular, we recently reported that the multicomponent coupling of imines, acid chlorides, and carbon monoxide with unsaturated substrates can provide a route to assemble various useful heterocycles (pyrroles, imidazoles, imidazolines, or b-lactams) by the formation of the münchnones (3).…”
Section: Yingdong Lu and Bruce A Arndtsen*mentioning
confidence: 99%
“…100 8C, 60 bar), and the use of strong acid additives. These are presumably related to the poor ability of palladium to directly activate the C À O bond of 1, which instead is believed to be converted into a more reactive iminium salt intermediate (4) under the reaction conditions (Scheme 2). [1,3] Whereas we have noted mild routes to CÀO carbonylation with a-phenoxyamides, the reaction still employs relatively strong Lewis acids (e.g.…”
Section: Yingdong Lu and Bruce A Arndtsen*mentioning
confidence: 99%